Using Arduino Alvik for Learning Robotics in Educational Environments - Buiar, André Luiz; Lima, Julia Correa; Rohrich, Ronnier Frates; Oliveira, André Schneider de (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper presents Alvik, a new educational robotics platform developed by Arduino, as a promising resource for future robotics education. We explore how Alvik's versatility and broad application potential make it particularly valuable for classroom use. The article outlines key concepts and features of the robot, assessing its suitability as an effective educational tool in the field of computational robotics, especially considering its user-friendly design. Additionally, we propose an original teaching track layout aimed at engaging students through a dynamic and innovative learning experience.